IMPLEMENTASI PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KOMPETENSI PERBAIKAN SISTEM BAHAN BAKAR SISWA PUSDIKLAT - Utama, Nyoman Yoga; Mindarta, Erwin Komara; Komarudin, Komarudin; Suhartadi, Syarif (Universitas Negeri Yogyakarta, 2024)
The Center for Automotive Technical Education and Training (PUSDIKLAT) serves as a bridge to produce graduates with specific skills aligned with the needs of businesses and industries (DU/DI). In this context, PUSDIKLAT must prepare effective learning strategies across all Automotive Engineering subjects, including Fuel System Repair, a core subject in the Automotive Engineering Department. However, the current learning approach remains conventional, resulting in the need to improve student performance and motivation. To address this issue, this study aims to enhance student competence by implementing Problem-Based Learning (PBL) at PUSDIKLAT SUZUKI, State University of Malang, in the subject of vehicle fuel system repair. This research adopts a Classroom Action Research (CAR) method, utilizing instruments such as pre-tests, post-tests, field notes, and interview guidelines. The study was conducted over four meetings across two cycles. The results showed significant improvement: in the first cycle, the mastery level was 56% for knowledge and 48% for skills, which increased to 100% in the second cycle. The improvement in percentages across cycles is evident from the average scores. In the first cycle, the average score was 74 for knowledge and 72 for skills, which increased to 81 in the second cycle, exceeding the minimum criterion of 75. Additionally, student motivation and perceptions of PBL application were positive. These findings indicate that PBL effectively improves students' knowledge, skills, and motivation in learning fuel system repair.